Comparative susceptibility and immune responses of Asian and European honey bees to the American foulbrood pathogen, Paenibacillus larvae - Sasiprapa Krongdang (2019)
© 2018 Institute of Zoology, Chinese Academy of Sciences American foulbrood (AFB) disease is caused by Paenibacillus larvae. Currently, this pathogen is widespread in the European honey bee—Apis mellifera. However, little is known about infectivity and pathogenicity of P. larvae in the Asiatic cavity-nesting honey bees, Apis cerana. Moreover, comparative knowledge of P. larvae infectivity and pathogenicity between both honey bee species is scarce. In this study, we examined susceptibility, larval mortality, survival rate and expression of genes encoding antimicrobial peptides (AMPs) including defensin, apidaecin, abaecin, and hymenoptaecin in A. mellifera and A. cerana when infected with P. larvae. Our results showed similar effects of P. larvae on the survival rate and patterns of AMP gene expression in both honey bee species when bee larvae are infected with spores at the median lethal concentration (LC50) for A. mellifera. All AMPs of infected bee larvae showed significant upregulation compared with noninfected bee larvae in both honey bee species. However, larvae of A. cerana were more susceptible than A. mellifera when the same larval ages and spore concentration of P. larvae were used. It also appears that A. cerana showed higher levels of AMP expression than A. mellifera. This research provides the first evidence of survival rate, LC50 and immune response profiles of Asian honey bees, A. cerana, when infected by P. larvae in comparison with the European honey bee, A. mellifera.